SOCIO-POLITICAL DISCOURSE IN SELECTED POEMS OF ODIA OFEIMUN (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
This study interrogates selected poems from three of Odia Ofeimun’s poetry collections, namely The Poet Lied, A Handle for the Flutist, and London Letters, and argues that the socio-political conditions of the Nigerian state as represented in the poetry is ignoble and anathema to positive societal development. It is in this regard that it is posited in the study that the poet unmistakably establishes for his readers the condition of the socio-political landscape of his country that serves as the canvass of his poetry. The study argues that the poet, being a student of his society and a committed poet who belongs to a generation of writers that believe literature should serve as a means to raise a people’s consciousness, the working people that is, to their place in society, unequivocally exposes the rottenness in the land. It is equally established that the poet makes it manifestly clear that the ruling class shows little or no pity for the toiling masses; the working people are treated poorly and given scant attention in the society as their interests are peripheral in the consideration of the ruling class. It is the conclusion in the paper that the poet’s objective of writing the way he does is to mobilize the people to rise up in their own defense in the face of their dehumanizing treatment. The essay adopts the Marxist theory in its investigation of its objective.